Impact of new information technology on librarian effectiveness in performing library functions:a case of Nigerian university libraries (2000)
Information technologies have been found to play an important role in various functions in the library, and for library users. Academic libraries like all other libraries make use of various information technologies in the academic libraries in Nigeia and examines the effectiveness of librarians in the use of these information technologies. The study determines the impact made by library-automated system, electronic data systems and services in academic libraries. Twelve federal universities in Nigeria were randomly selected for this study, and the questionnaire instrument was used to collect data. The result of this study indicates the following; that there is a significant difference in the use of new information technologies and librarians' effectiveness, that there is nosignificant contribution to librarians should be properly trained in the use of thses new information technologies.Provision should also be made for each academic librarian to have a personal computer (PC) available for constant use by these librarians.